Tomato water stress index as a function of irrigation depths - Silva, Cicero J. da; Silva, Cesar A. da; Freitas, Carlos A. de [UNESP]; Golynski, Adelmo; Silva, Luiz F. M. da; Frizzone, Jose A. (Univ Federal Campina Grande, 2018)
Infrared thermometry allows evaluating plants under water stress, by measuring the canopy temperature, without the need of physical contact with the leaves. The aim of this study was to determine the water stress index of the tomato crop for industrial processing (Hybrid 'BRS Sena'), as a function of irrigation depths applied by subsurface drip irrigation, in Southern Goias, Brazil, in 2015 and 2016. The experiment was conducted in a randomized block design, with four replicates. The treatments consisted in five irrigation depths: 50, 75, 100, 125 and 150% of crop evapotranspiration. The water stress index of the tomato crop was evaluated using two methodologies, as a function of the canopy temperature, air temperature and other local meteorological parameters, as well as the relationship between water stress index and crop yield. Theoretical and empirical methods estimate CWSI similarly in tomato. In the hottest hours of the day, even under adequate soil moisture conditions, the 'BRS Sena' tomato showed CWSI above 0.2. CWSI is a good indicator to evaluate the water status of the tomato crop for industrial processing and to recommend the moment of irrigation. The higher the CWSI, the lower the yield of 'BRS Sena' tomato.
Keywords: subsurface drip; industrial tomato; canopy temperature; Solanum lycopersicom L.; crop evapotranspiration